Menyoal Makna Netralitas Pegawai Negeri Sipil dalam Undang-Undang Nomor 5 Tahun 2014 Tentang Aparatur Sipil Negara - Sudrajat, Tedi; Mulya Karsona, Agus (Jurnal Media Hukum, 2016)
Problems of neutrality of civil servants will always occur when the meaning of neutralityÂ  is not in sync with the norms. In order to evaluate governance, the meaning of neutrality should be broader and more functional towards the legal relationship in the context of public official relation in the field of civil servants law. Substantially, the focus of Law Number 5 Year 2014 concerning Civil State Apparatus just make civil servants as an object of neutrality, regardless of the dynamic activity of practical politic intervention. It should be underlined that the role of civil servants in government always correlate with many interested parties. If neutrality is not matched by standard criteria and restrictions, it is very possible neutrality principle only be a slogan with minimum implementation.